The Need to Label Genetically Modified Products from the Perspective of Community Health and Consumer Rights: A Review - Ehsan Moshkelgosha; Seyed Mohammad Hosseini (Islamic Azad University, 2016)
Introduction: The production and supply of genetically modified organisms is one of the issues that have led to many legal, health and environmental issues. This research attempts to study the requirement for labeling of genetically modified products in terms of consumer rights and community health. Methods: This Review Article survey results researches during years from 2002 to 2016 with key word society health, genetic modified products, consumer rights, labeling at databases of Google scholar, SID, Iranmedex, Medline, PubMed, Springer, Science Direct, ProQuest, Magiran, MSRT journals system, Iran medical journals information system and ISC. Results: According to reported studies, genetically modified products may affect in human health, environment and society. Labeling of genetically modified products Cause to creating more awareness of consumer and provides informed choice of consumer. The responsibility of genetically modified products is Non-harmfulness is duty of producers and suppliers of genetically modified products. Conclusion: in line with protecting human and society health, According to consumer rights and environmental law and especially the precautionary principle, the labeling of genetically modified products is necessary.